IMPLEMENTASI PERDA NOMOR 4 TAHUN 2008 DALAM PROSES PEMBANGUNAN INFRASTRUKTUR DI NAGARI KOTO BARU KECAMATAN SUNGAI TARAB DALAM PERSPEKTIF SIYASAH DUSTURIYAH - Yani Trisna; Sulastri Caniago; Dian Pertiwi (Institut Agama Islam Negeri Batusangkar, 2021)
This study examines the implementation of Perda No. 4 of 2008 in the process of infrastructure development in Nagari Koto Baru, Sungai Tarab District by looking at the Siyasah Dusturiyyah perspective. This research was conducted using field research methods. From the results of the study it can be concluded that the implementation of Tanah Datar Regional Regulation Number 4 of 2008 in the process of infrastructure development in Nagari Koto Baru, Sungai Tarab District is appropriate and well implemented in accordance with the provisions contained in Article 106 of Tanah Datar District Regulation Number 4 of 2008 concerning Nagari . Meanwhile, Siyasah Dusturiyah's review regarding the implementation of Tanah Datar Regional Regulation Number 4 of 2008 in the process of infrastructure development in Nagari Koto Baru, Sungai Tarab District is appropriate and in line with the principles of deliberation. Whereas the executor of the Law, namely the executive, is also referred to in the siyasah dusturiyah as sulthah tanfidziyah which discusses the issue of Imamat or leadership in the Nagari Koto Baru Government who has run the government in accordance with the principles of fath adz-dzari'ah and the sixth rule of branch fiqh rules according to the majority of scholars who become a reference for leaders and government in making policies related to the people.